Nieoczywiste…? Wybrane plakaty Andrzeja Pągowskiego do polskich filmów fabularnych o artyście i sztuce - Grodź , Iwona (Załącznik Kulturoznawczy, 2024)
The subject of the text are less known posters by Andrzej Pągowski (born 1953) for Polish films about artists and art. The aim of the analysis is to present the strategies of attracting interest used by poster artists using specific examples of Polish films about artists and art. An excellent way to effectively influence the film viewers is the use, in this type of messages, of references (also à rebours) to the Aristotelian triad: ethos, pathos and logos. In the case of film posters, the medium of these practices are image and text. In the visual layer, attracting attention comes down primarily to the choice of people, things and spaces that are presented on the poster, the use of specific colors, the play with chiaroscuro, close-ups or non-obvious film frames. Research material: posters for selected films by Andrzej Pągowski: Baritone (1984), dir. J. Zaorski, Scribbler (1985), dir. W.J. Has, Two Moons (1993), dir. A. Barański. Methodology: phenomenology, semiotics.